Why has Japan 'succeeded'? - "Morishima , Michio" (Combridge, 1985)
his book, by a distinguished Japanese economist now resident in the West, offers a new interpretation of the current success of the Japanese economy. By placing the rise of Japan in the context of its historical development, Michio Morishima shows how a strongly-held national ethos has interacted with religious, social and technological ideas imported from elsewhere to produce highly distinctive cultural traits. While Professor Morishima traces the roots of modern Japan back as far as the introduction of Confucianism, Taoism and Buddhism from China in the sixth century, he concentrates his observations on the last 120 years during which Japan has had extensive contacts with the West. He describes the swift rise of Japan to the status of a first-rate power following the Meiji Revolution after 1867, in which Japan broke with a long history of isolationism, and which paved the way for the adoption of Western technology and the creation of a modern Western-style nation state; and a similarly meteoric rise from the devastation of the Second World War to Japan's present position. A range of factors in Japan's economic success are analysed: her characteristic dualistic social structure - corresponding to the divide between large and medium/small enterprises - the relations of government and big business, the poor reception of liberalism and individualism, and the strength of the Japanese nationalism. Throughout, Professor Morishima emphasizes the importance of the role played in the creation of Japanese capitalism by ethical doctrines as transformed under Japanese conditions, especially the Japanese Confucian tradition of complete loyalty to the firm and to the state. This account, which makes clear the extent to which the economic rise of Japan is due to factors unique to its historical traditions, will be of interest to a wide general readership as well as to students of Japan and its history.
Keywords: Japan-Industries-History